DETERMINATION OF PERMISSIBLE UPPER LIMIT OF STRENGTHENING OF ALLOY BT23 IN THE PROCESS OF THERMAL TREATMENT OF ARTICLES OF PLATE PIECES - V. N. Fedulov (Литьë и металлургия)
The influence of impact elasticity and specific work of crack resistance on fastness of plates with thickness 100 mm of alloy BT23 is studied.